Oxford Scholarship Online 2017
DOI: 10.1093/oso/9780198790266.003.0002
|View full text |Cite
|
Sign up to set email alerts
|

Stretching the Limits of Solidarity

Abstract: Germany had already made major reforms to social policy before the Great Recession. It had moved away from the traditional corporatist breadwinner welfare state model towards greater individual responsibility (private pensions and workfarist reforms, with sharp benefit cuts), and much more extensive support for childcare. Social investment and training measures have been much strengthened. These measures, carried out within a general framework of austerity and retrenchment, had increased employment, although t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Despite some in-depth reforms in the last decades, the German welfare system is still rooted in a Bismarckian tradition of social insurance. This statuspreserving system is still prevalent in the pension system and also in the unemployment protection scheme, albeit the Hartz-reforms in 2004 added a tax-financed, flat-rate unemployment protection layer and a generally stronger emphasis on self-responsibility was introduced (for an overview: Heuer & Mau, 2017). Research showed thatwhile increased individual responsibility was largely acceptedthe shift from status preservation towards tax-financed basic protection was received sceptically among the German population (eg Nüchter et al, 2010;Sachweh et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Despite some in-depth reforms in the last decades, the German welfare system is still rooted in a Bismarckian tradition of social insurance. This statuspreserving system is still prevalent in the pension system and also in the unemployment protection scheme, albeit the Hartz-reforms in 2004 added a tax-financed, flat-rate unemployment protection layer and a generally stronger emphasis on self-responsibility was introduced (for an overview: Heuer & Mau, 2017). Research showed thatwhile increased individual responsibility was largely acceptedthe shift from status preservation towards tax-financed basic protection was received sceptically among the German population (eg Nüchter et al, 2010;Sachweh et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Self‐administration has been weakened, and the coverage of social insurance increased, especially because of labour market developments. And, finally, in the 1990s, a whole new branch of social insurance was introduced, even though with “limited” powers (Heuer & Mau, , p. 42).…”
Section: Resultsmentioning
confidence: 99%
“…The increasing significance of family policies and social services, the associated move from the single‐wage‐earner norm to a dual‐breadwinner model, a growing role of basic income systems, and cuts in social insurance schemes are among the tendencies most often mentioned in research (cf. Blum & Kuhlmann, ; Heuer & Mau, ; Hinrichs, ; Leisering, ; Nullmeier, ; Seeleib‐Kaiser, ). Because of these developments, some researchers even question the classification of the German welfare state as “Bismarckian” or “conservative” and see the coming of a new hybrid, combining (fewer) conservative features with aspects of Scandinavian and liberal welfare states (Seeleib‐Kaiser, , p. 235; Leisering, , p. 242; Hinrichs, , p. 71; Blank, , pp.…”
Section: Introductionmentioning
confidence: 99%
“…The German welfare state, in contrast, did not experience such a harsh attack on its core institutions (for an overview see Heuer and Mau 2017). Although changes such as benefit reductions and increased co-payments were introduced in the 1980s and 1990s, the basic architecture of a corporatist status-maintenance-oriented welfare-state model remained intact.…”
Section: The Moral Economy Approach and The Regime Frameworkmentioning
confidence: 99%